2012
DOI: 10.1371/journal.pone.0029947
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR-Based Metabolic Profiling of Maternal and Umbilical Cord Blood Indicates Altered Materno-Foetal Nutrient Exchange in Preterm Infants

Abstract: BackgroundAdequate foetal growth is primarily determined by nutrient availability, which is dependent on placental nutrient transport and foetal metabolism. We have used 1H nuclear magnetic resonance (NMR) spectroscopy to probe the metabolic adaptations associated with premature birth.MethodologyThe metabolic profile in 1H NMR spectra of plasma taken immediately after birth from umbilical vein, umbilical artery and maternal blood were recorded for mothers delivering very-low-birth-weight (VLBW) or normo-ponder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 50 publications
(63 reference statements)
6
38
0
Order By: Relevance
“…Previous metabonomic studies corroborate our results, although on a smaller sample scale, where a general decrease of amino acids in maternal urine at gestational weeks 14–26 was observed in FGR cases ( n  = 10) compared to controls ( n  = 84) [9]. Significant differences in BCAA levels, along with other circulating amino acids, were also identified in plasma and cord blood studies of IUGR babies [8, 29]. The importance of BCAAs as predictive markers of gestational diabetes but also in non-pregnant populations of adiposity and type 2 diabetes is well established [27, 28, 30].…”
Section: Discussionsupporting
confidence: 89%
“…Previous metabonomic studies corroborate our results, although on a smaller sample scale, where a general decrease of amino acids in maternal urine at gestational weeks 14–26 was observed in FGR cases ( n  = 10) compared to controls ( n  = 84) [9]. Significant differences in BCAA levels, along with other circulating amino acids, were also identified in plasma and cord blood studies of IUGR babies [8, 29]. The importance of BCAAs as predictive markers of gestational diabetes but also in non-pregnant populations of adiposity and type 2 diabetes is well established [27, 28, 30].…”
Section: Discussionsupporting
confidence: 89%
“…The mechanisms relating N- acetyl glycoproteins to obesity and IPB, remain unclear; however, it is widely reported that high levels of adipose tissue can lead to systemic inflammation through release of cytokines such as interleukin-6, which could lead to an acute phase response [41]. Higher N- acetyl glycoprotein levels in NMR spectra of women with PB were also found in a study profiling maternal serum and cord blood at birth [42]. Spontaneous PB was specifically associated with higher urinary lysine, an essential amino acid that is limiting for growth, and is elevated in the plasma of premature infants [43].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Tea et al [16] explored the metabolic adaptations associated with preterm birth using a NMR-based metabolomic approach. PCA showed clear distinctions between maternal and cord plasma of all samples.…”
Section: Prematuritymentioning
confidence: 99%